2019
DOI: 10.1002/1873-3468.13671
|View full text |Cite
|
Sign up to set email alerts
|

UvrA and UvrC subunits of the Mycobacterium tuberculosis UvrABC excinuclease interact independently of UvrB and DNA

Abstract: The UvrABC excinuclease plays a vital role in bacterial nucleotide excision repair. While UvrA and UvrB subunits associate to form a UvrA2B2 complex, interaction between UvrA and UvrC has not been demonstrated or quantified in any bacterial species. Here, using Mycobacterium tuberculosis UvrA (MtUvrA), UvrB (MtUvrB) and UvrC (MtUvrC) subunits, we show that MtUvrA binds to MtUvrB and equally well to MtUvrC with submicromolar affinity. Furthermore, MtUvrA forms a complex with MtUvrC both in vivo and in vitro, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The functions of individual subunits of the E. coli UvrABC complex have been studied in greater detail using genetic, biochemical and structural approaches [1,11,12]. However, emerging evidence supports the notion that the catalytic and mechanistic features of the E. coli UvrABC repair complex are far from being universal in bacteria [1,11,12,37,53,58]. For example, M. tuberculosis is evolutionarily distant from E. coli and that only 41% of M. tuberculosis proteins have clear E. coli homologs [59], and we found that the overall sequence identity between MtUvrC and EcUvrC is 35.5%.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The functions of individual subunits of the E. coli UvrABC complex have been studied in greater detail using genetic, biochemical and structural approaches [1,11,12]. However, emerging evidence supports the notion that the catalytic and mechanistic features of the E. coli UvrABC repair complex are far from being universal in bacteria [1,11,12,37,53,58]. For example, M. tuberculosis is evolutionarily distant from E. coli and that only 41% of M. tuberculosis proteins have clear E. coli homologs [59], and we found that the overall sequence identity between MtUvrC and EcUvrC is 35.5%.…”
Section: Discussionsupporting
confidence: 54%
“…The K d values of MtUvrC for these substrates are in the same range as that reported for EcUvrC‐CTD [46]. Although firm evidence is lacking, it is likely that a dimeric form of MtUvrC binds to the DNA lesion site [58].…”
Section: Discussionmentioning
confidence: 56%
“…In addition, codon selection is common in both prokaryotes and eukaryotes and fundamentally influences the synthesis of a particular polypeptide and/or the accuracy of translation [ 67 ]. UvrABC excinuclease plays an important role in bacterial nucleotide excision repair [ 68 ]. In the present study, a non-syn mutation was found in the open reading frame of the excinuclease ABC subunit uvrB gene (Cthe_0309), where amino acid His was replaced by Arg at position 402 ( Table S10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, codon selection is common in both prokaryotes and eukaryotes and fundamentally influences the synthesis of a particular polypeptide and/or the accuracy of translation [69]. UvrABC excinuclease plays an important role in bacterial nucleotide excision repair [70]. In the present study, a Nsy mutation was found in the open reading frame of the excinuclease ABC subunit UvrB gene (Cthe_0309), where His was replaced by Arg at amino acid 402 (Table S6).…”
Section: Genomic Analysismentioning
confidence: 69%